Penerapan Model Pembelajaran Learning Cycle 5e untuk Meningkatkan Aktivitas dan Penguasaan Konsep Siswa Pada Mata Pelajaran PAI dan Budi Pekerti di SMA Negeri 1 Selong - Asmuni, Asmuni (Jurnal Paedagogy, 2020)
The aim of this research to implement the 5E learning cycle model to improve students activity and mastery of student concept of marriage in Islam.This research used designclassroomactionresearch which takes placetwo cycles. The subjects of this study were 32 students of class XII IPS-4. Data collection was carried out by the method of observation to obtain data on learning activities and test methods (evaluation) to obtain data on the level of mastery of students' concepts of marriage material in Islam given at the end of each cycle. The data collected was analyzed descriptively qualitatively. The results of the action research obtained are a) an increase in student learning activities, as indicated by all indicators of student activity, the percentage increases from cycle I to cycle II. If it is averaged each cycle, then the average cycle I obtained by 66% with good criteria, the average increase in cycle II by 81% with very good criteria, and b) increasing mastery of student concepts, shown by completing learning from cycle I by 78.13% (25 people) to the second cycle was 87.50% (28 people), and the class average from the first cycle was 85.14 to the second cycle was 93.68.